The 21st Century Cures Act: Perspectives of Clinicians in a Level-IV Neonatal Intensive Care Unit - Sullivan, Anne H. T.; Healy, Helen M.; DeGrazia, Michele; Toole, Cheryl; Hansen, Anne; Leeman, Kristen T. (American Journal of Perinatology, 2022)
Objective Our objective is to describe the implications, anticipated and perceived, by providers in a level-IV neonatal intensive care unit (NICU) with immediate patient access to inpatient notes and test results in the wake of the 21st Century Cures Act (CCA).Study Design Using a mixed-method approach in February 2021, a preimplementation survey of neonatologists, neonatal fellows, nurse practitioners, and neonatal nurses reported their perspectives on the new 21st CCA and how they anticipated that it would change their practices, and the experience of families in the NICU. In the follow-up to implementation, a postsurvey was completed by staff reporting their experiences in July 2021. Thematic analysis was performed.Results In the preimplementation survey, staff reported the greatest perceived benefits of the changes to be an increase in families' ability to be part of the care team and prepare questions, and faster discussion of results by the care team. Also, staff's highest concerns were that family members may incorrectly interpret results delivered electronically without the context provided by the care team and be overwhelmed by the amount of information available. In the postimplementation survey, staff reported that the Act had less impact on their practice than they had anticipated preimplementation.Conclusion To maximize benefits and limit burdens to families and staff, care teams should consider a thoughtful approach to information sharing with family members in compliance with the 21st CCA.Key Points
Keywords: electronic health information; neonatal intensive care unit; family-centered care; pediatrics